Long-Term Growth of Alfalfa Increased Soil Organic Matter Accumulation and Nutrient Mineralization in a Semi-Arid Environment - Song, Xin; Fang, Chao; Yuan, Zi-Qiang; Li, Feng-Min (Frontiers in Environmental Science, 2021)
Land use patterns and vegetation coverage in semi-arid areas of the Loess Plateau have undergone great changes due to the implementation of the “Grain for Green” project. The introduction of legume pasture species, such as alfalfa (Medicago sativa L.) and sweet clover (Melilotus officinalis L.), is one of the most efficient methods of vegetation restoration and reconstruction in this region. However, there is a need for an effective assessment of the root system distribution and its interaction with soil after long-term introduction. An experiment involving the introduction of alfalfa and sweet clover on abandoned farmlands was initiated in 2003 to assess the long-term effects. After 17 years, root and soil samples at depths of 0–20 and 20–60 cm were collected to characterize the root biomass, root carbon (C), nitrogen (N), and phosphorus (P), soil microbial biomass carbon (MBC) and nitrogen (MBN), soil organic carbon (SOC), and soil N and P. The results showed that the root biomass density of alfalfa in the 0–20 and 20–60 cm layers (63.72 and 12.27 kg m–3, respectively) were significantly higher than for sweet clover (37.43 and 8.97 kg m–3, respectively) and under natural abandonment (38.92 and 9.73 kg m–3, respectively). The SOC, total nitrogen (TN), total phosphorus (TP), available phosphorus (AP), nitrate-nitrogen (NO3–-N), MBC and MBN in the 0–20 and 20–60 cm layers were higher after alfalfa introduction compared with sweet clover introduction and natural abandonment, although the ammonia-nitrogen (NH4+-N) concentration in the 0–20 cm layer was lower. There were significantly positive correlations between root biomass density and both soil nutrients and microbial biomass, while there was a negative correlation between the soil NH4+-N and root biomass density. These results indicate that alfalfa root growth improved soil organic matter accumulation and nutrient mineralization. The accumulation and mineralization of soil nutrients also guaranteed root and microorganism growth. Therefore, it was concluded that alfalfa introduction will promote soil nutrients immobilization and mineralization and may enable sustainable land use in the semi-arid region of the Loess Plateau, China.